2023
DOI: 10.1111/ene.15788
|View full text |Cite
|
Sign up to set email alerts
|

Indication for molecular testing by multiplex ligation‐dependent probe amplification in parkinsonism

Abstract: Background and purpose:The monogenic forms of Parkinson's disease represent <10% of familial cases and a still lower frequency of sporadic cases. However, guidelines to orient genetic testing are lacking. The aim was to establish the interest of multiplex ligationdependent probe amplification (MLPA) as a primary screening test and to propose clinical criteria to guide genetic diagnostic tests for patients with suspected Mendelian Parkinson's disease.Methods: In all, 567 patients with parkinsonism from 547 unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is reasonable, therefore, to perform MLPA to screen for SVs first. [39] In our previous study, we combined MLPA with targeted resequencing/Sanger sequencing to analyze EOPD patients (n = 918) with an AAO younger than 50 years in a Japanese cohort. We identified that 6.4% of the patients harbored two variants in the PRKN gene, while 3.9% presented with a single variant.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable, therefore, to perform MLPA to screen for SVs first. [39] In our previous study, we combined MLPA with targeted resequencing/Sanger sequencing to analyze EOPD patients (n = 918) with an AAO younger than 50 years in a Japanese cohort. We identified that 6.4% of the patients harbored two variants in the PRKN gene, while 3.9% presented with a single variant.…”
Section: Discussionmentioning
confidence: 99%